The Intellectual Foundations of the English Benedictine Reform. - Gretsch, Mechthild (Cambridge Studies in Anglo-Saxon England, 25., 1999)
This book explores the intellectual foundations of the Benedictine reform in tenth-century England. It examines the importance of the vernacular at Bishop Æthelwold's influential Winchester school. Æthelwold's early career is also examined, showing the influence King Æthelstan's court had on intellectual and spiritual thought.